(untitled) (The Pakistan Development Review, 2002)
The issue of whether stock prices and exchange rates are related or not has received considerable attention after the East Asian crisis. During the crisis the countries affected saw turmoil in both currency and stock markets. If stock prices and exchange rates are related and the causation runs from exchange rates to stock prices, then the crisis in the stock markets can be prevented by controlling the exchange rates. Moreover, developing countries can exploit such a link to attract/stimulate foreign portfolio investment in their own countries. Similarly, if the causation runs from stock prices to exchange rates then authorities can focus on domestic economic policies to stabilise the stock market. If the two markets/prices are related then investors can use this information to predict the behaviour of one market using the information on other market.1 Most of the empirical literature that has examined the stock prices-exchange rate relationship has focused on examining this relationship for the developed countries with very little attention on the developing countries. The results of these studies are, however, inconclusive. Some studies have found a significant positive relationship between stock prices and exchange rates [for instance Smith (1992); Solnik (1987) and Aggarwal (1981)] while others have reported a significant negative relationship between the two [e.g., Soenen and Hennigar (1998)]. On the other hand, there are some studies that have found very weak or no association between stock prices and exchange rates [for instance, Franck and Young (1972); Bartov and Bodnor (1994)].